Advances in the Management of Diabetic Foot Ulcers - Canavan, Neil (MD Conference Express, 2008)
In an attempt to lower current rates of amputation due to diabetic foot ulcers, the foot care interest group of the American Diabetes Association has published updated management guidelines. This article reviews these literature-based recommendations.